Pengaruh Konsentrasi Kepemilikan, Risiko Pajak, dan Risiko Perusahaan Terhadap Agresivitas Pajak dengan Manajemen Laba Akrual Sebagai Moderasi - Engela Ananta; Nera Marinda Machdar (Pusat Riset dan Inovasi Nasional, 2024)
Companies perceive taxes as a burdensome expense, which can diminish potential profits. As corporate taxpayers, companies have a responsibility to pay taxes in accordance with applicable laws. Tax aggressiveness refers to tactics employed by companies to manage or manipulate the magnitude of the tax burden they must bear, aiming to reduce their actual tax obligations without violating the law. This research examines the relationship between ownership concentration, tax risk, and corporate risk on tax aggressiveness, with accrual earnings management as a moderation variable. Data analysis is conducted using descriptive statistics with a quantitative approach. The research findings indicate that ownership concentration, tax risk, and corporate risk positively influence tax aggressiveness. Additionally, accrual earnings management can weaken the impact of ownership concentration, tax risk, and corporate risk on tax aggressiveness.